Integrating health care and early years support for children and young people living in deprivation: a cost-effectiveness analysis of the Sparkbrook Children’s Zone integrated clinic versus usual primary care in Birmingham, UK - Ian Litchfield; Lorraine Harper; Mark Monahan; Christopher Bird; Melyda Melyda (BMJ Paediatrics Open)
Background Increased use of emergency and secondary care by children and young people, especially in deprived populations, drives increased costs in health and social care systems in rich country settings, without necessarily delivering quality care. This study aims to assess the potential cost-effectiveness of the Sparkbrook Children’s Zone (SCZ), a pilot clinic for children and young people which integrates health and early years support in a highly deprived area of Birmingham, the UK’s second city, compared with standard primary care.Methods A decision-analytic model taking a healthcare and partial social care perspective was developed using the best available, though limited, evidence from aggregated data of an ongoing pilot, published literature, expert opinions and assumptions. Effectiveness was measured as a proportion of patients attending the emergency department (ED). Deterministic and probabilistic sensitivity analyses were performed to assess the impact of parameter uncertainties.Results The integrated SCZ clinic may potentially be cost-effective based on this preliminary model-based analysis. The SCZ had a lower proportion of patients attending ED, 0.017 compared with 0.029 for standard primary care, reducing the proportion of ED visits by 0.012. The average cost of SCZ was £66.22 compared with £110.36 for standard primary care, leading to a cost saving of £44.08 per patient. This potential reduction in total costs resulted from fewer referrals to children’s social care and secondary medical services, including the ED. Extensive sensitivity analysis supported the indications that the intervention was likely to be cost-effective.Conclusion The SCZ shows the potential that integrating health and social care that is place-based is potentially cost-effective, with its early years support likely enhancing the cost-effectiveness of the intervention compared with standard primary care. Further robust data and trial evaluation are essential to confirm these findings, ensuring the scalability and sustainability of such programmes.